1990
DOI: 10.1248/cpb.38.1748
|View full text |Cite
|
Sign up to set email alerts
|

Increased .GAMMA.-aminobutyrate aminotransferase activity in brain of patients with Alzheimer's disease.

Abstract: In order to search for more proximal factors in the pathogenesis of Alzheimer's disease, we studied the activities of various enzyme in the brains of patients, as well as control cases, by postmortem autopsy. In addition to the findings already known, such as the increase in prolyl endopeptidase (post-proline cleaving enzyme, PPCE) activity and the decrease in kallikrein activity, we found, anew, an increase in aminobutyrate aminotransferase (GABA-T) activity in the Alzheimer brain. This may be an important im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 1 publication
0
25
0
Order By: Relevance
“…The result is in sharp disagreement with the only report previously published on GABA-T activity in the brains of patients with AD. Thus, Aoyagi et al (1990) found a significantly increased GABA-T activity in the occipital lobe in brain of patients with AD (510% of the control value). We have no explanation for this discrepancy, but it is notable that their activities were 10-20-fold lower than usually found (Maitre etal., 1979;White and Faison, 1980;Sherif etal., 1991).…”
Section: Discussionmentioning
confidence: 81%
“…The result is in sharp disagreement with the only report previously published on GABA-T activity in the brains of patients with AD. Thus, Aoyagi et al (1990) found a significantly increased GABA-T activity in the occipital lobe in brain of patients with AD (510% of the control value). We have no explanation for this discrepancy, but it is notable that their activities were 10-20-fold lower than usually found (Maitre etal., 1979;White and Faison, 1980;Sherif etal., 1991).…”
Section: Discussionmentioning
confidence: 81%
“…A reduction in the concentrations of GABA has been implicated not only in the symptoms associated with epilepsy (12,13) but also with several other neurological diseases such as Huntington's chorea (14), Parkinson's disease (15), Alzheimer's disease (16), and tardive dyskinesia (17). Administration of GABA peripherally is not effective, because GABA, under normal conditions, cannot cross the blood-brain barrier; however, several other approaches have been taken to increase the brain concentrations of GABA.…”
mentioning
confidence: 99%
“…GABA is a major inhibitory neurotransmitter in the mammalian CNS. Low levels of GABA have been implicated in symptoms associated with epilepsy, convulsions, Parkinson's, Alzheimer's and Huntington's diseases [40][41][42][43]. The PLP-dependent enzyme DOPA decarboxylase (also known as aromatic L-amino acid decarboxylase (AAAD)) catalyzes the synthesis of dopamine via decarboxylation of L-3,4-dihydroxyphenylalanine (L-DOPA).…”
Section: Plp-dependent Enzymes and Brain Functionmentioning
confidence: 99%